Characterization and Quantification of Betasatellites Research from Google Scholar Using a Bibliometric Approach - Ahmad, Syed Ishfaq; Nasar, Zeeshan; Ullah, Zaib; Akhtar, Naeem; Akbar, Fazal; Ahmad, Nisar (Advancements in life sciences, 2021)
Background: Begomoviruses belongs to the family Geminiviridae. These viruses are associated with various satellite DNA molecules (alpha satellites, delta satellites, and betasatellites).Methods: The standardized search strategy was applied to get the research output regarding betasatellites worldwide for bibliometric analysis. Google scholar database was used to collect the data regarding betasatellites research from past 1997 to June 2018.Results: A total of 213 documents regarding the studied subject were identified, out of which the maximum number of documents 153 (71.83%) were found to have been published in the form of original research articles. The common language of publications 208 (97.65%) was English. The results declare that the number of publications shows an increase from 1997 to 2014, with the maximum number of publications in 2014. The top 10 productive countries based on the maximum number of publications were India 83 (38.96%), Pakistan 66 (30.98%), China 26 (12.20%) followed by some other countries. USA and Oman were the top collaborative countries with Pakistan respectively.Conclusion: For all the analyzed documents the total number of citations was 3564 with an average of 16.73 citations per document. The journal “Virus Genes” was the most prolific journal based on a maximum number of publications on the studied subject. Robert William Briddon and Shahid Mansoor were the most productive scientists, and the National Institute for Biotechnology and Genetic Engineering (NIBGE) was the most productive institute regarding the studied subject. This study shows that India, Pakistan, the USA, and China play an important role in the area of beta satellite research.Keywords: Betasatellites; Bibliometric Analysis; Begomoviruses